Assessment of valvular heart disease by cardiovascular magnetic resonance imaging: a review. - Christiansen, J; Karamitsos, T; Myerson, S (2011)
CMR is a comprehensive non-invasive tool capable of evaluating all aspects of valvular heart disease. It has advantages over echo including direct quantification of regurgitant lesions, highly accurate assessment of ventricular size and function, visualisation myocardial scar, and interrogation of extracardiac abnormalities. Although these gains can be realised with current scanning techniques, CMR's full potential has yet to be realised, and further studies of clinical outcomes are needed before CMR data can be integrated into the management algorithms for patients with significant valvular lesions.